Assessment Structuring in the Problem Based Learning Model in Sociology Learning at SMAN 1 Gurah - Younita, Dinda Putri; Pratiwi, Seli Septiana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Learning is a process in which a person's environment is intentionally arranged to enable individuals to engage in certain behaviors under specific conditions or to generate responses to specific situations. One learning model widely used to involve active student involvement is Problem Based Learning (PBL). Based on the results of data collection on learning patterns for sociology subjects at SMAN 1 Gurah, it was found that in learning practices there are still several problems, especially in terms of assessment. Therefore, this study was conducted to describe the process of preparing assessments by grade XI teachers in implementing the Problem Based Learning model at SMAN 1 Gurah and identify obstacles that arise along with strategies used to overcome them. By using observation, interview and documentation methods. The resulting data shows that the application of assessments in the PBL model at SMAN 1 Gurah has led to meaningful learning practices as stated by Ausubel, although it still requires strengthening in pedagogical communication and development of assessment literacy so that assessments can function optimally as a means of supporting learning and supporting the Pancasila student profile.